Toxicomania na psicose: os usos que o psicótico faz da droga - Helena Greco Lisita (2010)
This work focuses on the interface between toxicomania and psychosis. In recent years, the general practice has revealed a growing number of psychotic subjects who are users of illicit drugs, which leads us to reflect upon the partnership between the psychotic and the drug as a facet of the interweaving of the psychosis and the modern world. The addiction to drugs may overcast, for some time, the diagnosis issue. This is a delicate aspect of the treatment of the psychotic patient who regularly uses illicit drugs, pointing to the extreme importance of the spotting of the function of the drug for the subject in the determination of the differential diagnosis. We start with the hypothesis that the use of the drug in psychosis cannot be thought of in the same way as in neurosis; thus, one may question the validity of the term toxicomania such as is used in the neurosis field for psychosis. While toxicomania in neurosis is related with the rupture with phallic jouissance, leading to an unregulated usage, without limits and without signification of the drug, in psychosis this rupture is given beforehand: it is a structural condition caused by the foreclosure of the Name-of-the-Father significant. As a result, the drug in psychosis seems to have a clear character related to a very specific function, which is the treatment of the jouissance without signification that invades the subject. To support this hypothesis we will investigate the usages that the psychotic makes of the drug, his relation with the practices of consumption of modern society and its implications in the possible treatment of the cases of psychosis in which the toxicomania is present, using the psychoanalytic concepts proposed by Freud and Lacan.